2010
DOI: 10.1038/ejhg.2010.69
|View full text |Cite|
|
Sign up to set email alerts
|

Linkage and candidate gene studies of autism spectrum disorders in European populations

Abstract: the EU Autism MOLGEN Consortium 8Over the past decade, research on the genetic variants underlying susceptibility to autism and autism spectrum disorders (ASDs) has focused on linkage and candidate gene studies. This research has implicated various chromosomal loci and genes. Candidate gene studies have proven to be particularly intractable, with many studies failing to replicate previously reported associations. In this paper, we investigate previously implicated genomic regions for a role in ASD susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 49 publications
(43 reference statements)
3
67
0
4
Order By: Relevance
“…Characterization of the M867I missense mutation revealed no detectable effect on GluK2 receptor gating (Han et al, 2010), but revealed a modest ∼1.6-fold slowing of the desensitization time course. Additional SNP association studies on various populations support a role of GRIK2 in autism (Shuang et al, 2004;Dutta et al, 2007;Kim et al, 2007;Holt et al, 2010;Casey et al, 2012;Griswold et al, 2012). …”
Section: Kainate-selective Glutamate Receptorsmentioning
confidence: 94%
“…Characterization of the M867I missense mutation revealed no detectable effect on GluK2 receptor gating (Han et al, 2010), but revealed a modest ∼1.6-fold slowing of the desensitization time course. Additional SNP association studies on various populations support a role of GRIK2 in autism (Shuang et al, 2004;Dutta et al, 2007;Kim et al, 2007;Holt et al, 2010;Casey et al, 2012;Griswold et al, 2012). …”
Section: Kainate-selective Glutamate Receptorsmentioning
confidence: 94%
“…88 Association analysis showed strong coupling of MKL2 (MKL/myocardin-like 2) and TSN with autism in at least two European populations, Finnish and Northern Dutch ones. This raises the question: does TSN have a direct role in the development of this or any other diseases and if so, what are potential mechanisms of its function?…”
Section: Discussionmentioning
confidence: 99%
“…The RELN gene encodes a large extracellular matrix protein that organizes neuronal positioning during corticogenesis and is regulated by epigenetic mechanisms. Several independent studies have shown an association between RELN and ASD (Skaar et al, 2005;Ashley-Koch et al, 2007;Holt et al, 2010). Interestingly, reduced levels of reelin and its isoforms have been previously shown in autistic twins and their first degree relatives (Fatemi et al, 2005).…”
Section: Epigenetic Contributionsmentioning
confidence: 90%